Development and Functional Evaluation of a Web-Based Medical Equipment Maintenance Reminder System Integrated with Telegram Notifications - Mukhamad Firdaus Ferdiansyah; Rahma Ajeng Puspitasari (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2026)
Proper maintenance of medical equipment is essential for ensuring patient safety and clinical operational continuity, yet traditional manual documentation often leads to missed maintenance schedules. This research aims to develop and functionally evaluate a web-based Computerized Maintenance Management System (CMMS) integrated with Telegram notifications. The system was developed using the Waterfall software development model, utilizing XAMPP (PHP and MySQL) for backend management and the Telegram Bot API via webhook for automated alert delivery. The functional evaluation was conducted in a prototype environment using black-box testing and API response time analysis. Results demonstrated that the system successfully automates maintenance scheduling and delivers real-time notifications with a 100% success rate across all functional test cases. While this study confirms the technical reliability of the prototype in a controlled environment, further clinical deployment is required to measure its impact on operational efficiency. It is concluded that this digital solution provides a functional and reliable baseline for improving medical equipment management in healthcare facilities.